The influence of CAR, LDR, OER, and Bank Size on NPL mediated by GCG in KBMI III and IV - Yusuf, Maulana; Salim, M. Noor (International Journal of Entrepreneurship and Business Management, 2025)
The objective of this research is to examine how CAR, LDR, OER, and bank size affect NPL. By considering the role of GCG as a mediating or intervening variable, this research will do so. This research involves commercial banks in Indonesia whose populations fall into the KBMI categories 3 and 4, and the sample consists of 13 banks. This study uses panel data regression. The analysis results show that CAR and bank size do not have a significant impact on NPL, whereas LDR, OER, and GCG have a significant impact. These results indicate that liquidity management and operational efficiency play an important role in controlling credit risk. In addition, the implementation of good GCG can improve the quality of banking credit. Therefore, to reduce credit risk and enhance financial stability, banks must strengthen corporate governance